2019
DOI: 10.15578/iaj.14.2.2019.47-54
|View full text |Cite
|
Sign up to set email alerts
|

GONAD DEVELOPMENT OF SANDFISH (Holothuria scabra) FED WITH VITAMIN E-SUPPLEMENTED DIET

Abstract: The experiment was conducted to evaluate the effect of vitamin E on the gonad development of sandfish, Holothuria scabra. Four experimental diets were formulated to contain different levels of vitamin E, i.e. 0, 150, 300, and 450 mg/kg diet. Dry diets were prepared at the same protein level (14%). The experiment was arranged in a completely randomized design with four treatments and three replicates. Before the experiment started, the internal organs of broodstock were removed (evisceration) by injecting KCl 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…In the present study, both male and female koi carp exhibited higher growth performance indices only when fed with feed containing 200 mg/kg of vitamin E. The present result was in accordance with James et al (2008); Muchlisin et al (2016), and Sembiring and Hutapea (2019) who inferred that vitamin E at 300 mg/kg feed had the best weight gain and specific growth rate in goldfish ( Carassius auratus ), Javan mahseer ( Tor tambra ) and sand fish ( Holothuria scabra ) respectively. The authors also suggested that vitamin E affected the gonadal development, leading to gain average body weight in fish species.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, both male and female koi carp exhibited higher growth performance indices only when fed with feed containing 200 mg/kg of vitamin E. The present result was in accordance with James et al (2008); Muchlisin et al (2016), and Sembiring and Hutapea (2019) who inferred that vitamin E at 300 mg/kg feed had the best weight gain and specific growth rate in goldfish ( Carassius auratus ), Javan mahseer ( Tor tambra ) and sand fish ( Holothuria scabra ) respectively. The authors also suggested that vitamin E affected the gonadal development, leading to gain average body weight in fish species.…”
Section: Discussionsupporting
confidence: 93%
“…It is also to be noted that the next highest GSI was found in koi carps fed with feed containing vitamin E at 600 mg/kg feed. In addition, studies reported by Sembiring and Hutapea (2019) in sand fish (Holothuria scabra) and Muslimin et al (2020) in climbing perch (Anabas testudineus) have mentioned that GSI was found to be improved after higher inclusion of vitamin E in diets. Therefore, it can be inferred that both vitamins C and E were able to produce higher GSI in males only at fish fed with diets containing higher inclusion rate of vitamins.…”
Section: Gonadosomatic Index In Koi Carpmentioning
confidence: 93%